Characterising the mechanism of DCUN1D1 activity in prostate cancer and identifying DCUN1D1 inhibitors for prostate cancer treatment - Vava, Akhona (International Centre for Genetic Engineering and Biotechnology, 2022)
DCUN1D1 is an E3 ligase of the neddylation pathway. It mediates the posttranslational modification of majority of the cullin family of proteins with NEDD8. This activity is known to enhance ubiquitination of the cullin RING E3 ligases, however, the extent of the impact of DCUN1D1's activity is underexplored. Studies performed previously in our lab demonstrated the role of DCUN1D1 in prostate cancer in vitro and in vivo. We also identified potential inhibitors of DCUN1D1 which inhibited the proliferation of prostate cancer cells in a DCUN1D1-specific manner. This study seeks to determine the mechanism of action of DCUN1D1 in prostate cancer and to identify DCUN1D1 inhibitors using a proteomics approach. Immunoprecipitation-coupled mass spectrometry was performed to identify DCUN1D1 binding partners and we identified some known substrates of DCUN1D1 in the form of cullin 3, cullin 4B and cullin 5. We also observed that the DCUN1D1 pulldown products implicated the ubiquitin proteasome pathway, transcription, lipid metabolism and inflammatory pathways. SILAC quantitative proteomics analysis was also performed to determine the proteins that were differentially expressed in DU145 DCUN1D1 knockdown cells relative to DU145 control cells. Interestingly, we did not identify the cullin proteins or classical components of the neddylation pathway but identified the ubiquitin activating enzyme, UBA1. We also found that dysregulation of DCUN1D1 in prostate cancer led to a dysregulation in translation-related and protein processing activities such as dysregulation of eukaryotic protein translation, and protein processing in the endoplasmic reticulum. We also observed the recurrence of the WNT signalling pathway across the proteomics approaches. This culminated in the exploration of the mechanism of action of DCUN1D1 in prostate cancer using changes in protein expression as measured by western blot analysis. Significantly, we determined that DCUN1D1 mediates its mechanism of action in prostate cancer, through the neddylation pathway and preferential neddylation of cullin proteins. We also observed that knockdown of DCUN1D1 in prostate cancer led to the dysregulation of the ubiquitination and WNT/β-catenin pathways. Furthermore, advanced connectivity map analysis was performed to identify potential inhibitors of DCUN1D1 based on a proteomics approach. The drugs found to strongly connect with the DCUN1D1 knockdown signature included kinase inhibitors and anti-inflammatory agents. The above observations could lead to improved understanding of DCUN1D1 and its potential for molecular target based treatment of prostate cancer.